Statics of deformable solids - Bisplinghoff, Raymond L. (Dover books on engineering, 2014)
"Well-written, thoughtfully prepared, and profusely illustrated, this text by the prominent experts provides a full exposition of fundamentals of solid mechanics and principles of mechanics, statics, and simple statically indeterminate systems. Additional topics include strain and stress in three-dimensional solids, elementary elasticity, stress-strain relations for plastic solids, and energy principles in solid continuum."--